Acerca de los estudios sobre China en el Perú - Aquino Rodríguez, Carlos (2013)
In this article a look is given to the state of china studies in Peru. the asian country is becoming more important to the Peruvian economy now, and the traditional emphasis on studies of chinese immigration to Peru is given way to studies about Peru-china economic relationship. In the future more studies on this theme will be seen with the addition that a group of experts with knowledge of chinese language will appear.